2018
DOI: 10.14710/metana.v14i2.11341
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Minyak Goreng Bekas Menjadi Sabun Mandi

Abstract: Rekayasa produk limbah untuk mengurangi pencemaran dapat memberikan nilai lebih terhadap produk yang di hasilkan. Upaya pemanfaatan limbah minyak goreng bekas untuk diolah menggunakan rekayasa proses menjadi produk yang lebih berguna berupa sabun mandi. Penelitian ini dilakukan untuk mengkaji pengaruh konsentrasi NaOH dan suhu proses terhadap kualitas produk sabun mandi. Pada tahap persiapan, minyak goreng bekas dibersihkan dari pengotornya melalui proses filtrasi dan penetralan dengan larutan NaOH. Minyak gor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
2
0
5
Order By: Relevance
“…In that study it was found that the concentration of KOH had a significant effect on free alkali, the higher the KOH concentration the higher the value of the free alkali liquid soap produced. Similar results were also shown by Prihanto and Irawan 20) .The results showed that increasing the concentration of NaOH would increase the levels of free alkali present in the soap. This happens because the greater the concentration of NaOH added, the more NaOH is added so that more NaOH is left from the lathering reaction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In that study it was found that the concentration of KOH had a significant effect on free alkali, the higher the KOH concentration the higher the value of the free alkali liquid soap produced. Similar results were also shown by Prihanto and Irawan 20) .The results showed that increasing the concentration of NaOH would increase the levels of free alkali present in the soap. This happens because the greater the concentration of NaOH added, the more NaOH is added so that more NaOH is left from the lathering reaction.…”
Section: Discussionsupporting
confidence: 87%
“…Waste cooking oil used for making dishwashing liquid soap is usually cooking oil with three times usage. Waste cooking oil must be purified before being processed into soap 20) . One study that examined the manufacture of liquid soap from waste cooking oil research using a completely randomized design with a single factor, KOH concentration consisting of 3 levels, namely 25%, 30%, and 35% 8) .…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian tentang pemanfaatan Minyak goreng bekas menjadi berbagai diversifikasi produk sudah dilakukan diantaranya oleh (Prihanto & Irawan, 2018) tentang upaya pemanfaatan limbah minyak goreng bekas untuk diolah menggunakan rekayasa proses menjadi produk yang lebih berguna berupa sabun mandi, selanjutnya (Suarsa, 2018) (Pujiati, 2018). Selain itu Limbah minyak goreng/jelantah yang dibuang ke perairan dapat menyebabkan rusaknya ekosistem perairan karena meningkatnya kadar Chemical Oxygen Demind (COD) serta Biological Oxygen Demind (BOD) yang disebabkan tertutupnya permukaan air dengan lapisan minyak sehingga sinar matahari tidak dapat masuk ke perairan, akibatnya biota-biota perairan mengalami kematian yang akhirnya akan mengganggu ekosistem perairan tersebut (Haryono et al, 2010…”
Section: Pendahuluanunclassified
“…Minyak jelantah berpotensi sebagai bahan baku pembuatan sabun dengan dilakukan pengolahan atau pemurnian terlebih dahulu. Pengolahan atau pemurnian minyak jelantah dapat dilakukan melalui filtrasi (penyaringan) dan adsropsi menggunakan karbon aktif [3]. Minyak goreng bekas oleh masyarakat Desa Bugangan biasanya langsung dibuang ke lingkungan sehingga dapat menyebabkan pencemaran air maupun tanah.…”
Section: Pendahuluanunclassified